(1291) A programming method for Quasi and explicitly Quasi-concave minimum programming problem طريقة برمجة لمسألة البرمجة الدنيا شبه المقعرة وشبه المقعرة الصريحة - Omar, Amani (The Institute Of National Planning., 2018)
In the fifties, the theory of nonlinear programming was almost limited to problems in which the consraints and the objective functions were convex. In the sixties, it was gradually recognized that for most of the theorems to hold and for many of the methods to work, only some weaker property of convex.